Exploring the roots of digital and media literacy through personal narrative - Hobbs, Renee (Temple University Press, 2016)
"Exploring the Roots of Digital and Media Literacy through Personal Narrative provides a wide-ranging look at the origins, concepts, theories, and practices of the field. This unique, exciting collection of essays by a range of distinguished scholars and practitioners offers insights into the scholars and thinkers who fertilized the minds of those who helped shape the theory and practice of digital and media literacy education. Each chapter describes an individual whom the author considers to be a type of "grandparent." By weaving together two sets of personal stories--that of the contributing author and that of the key ideas and life history of the historical figure under their scrutiny--major concepts of digital media and learning emerge."--